Chinese martial arts cinema [ the Wuxia tradition - Teo, Stephen (Traditions in world cinema, 2009)
A study of the Chinese martial arts film focusing on the wuxia (martial chivalry) genre from its beginnings in the Shanghai cinema of the late 1920s to Ang Lee's Crouching Tiger, Hidden Dragon (2000)